Diversity of fish species in Boi river basin, Vietnam - Mai Huong, Ngo Thi; Duc, Nguyen Huu (Academia Journal of Biology, 2013)
The survey on fishes in Boi river basin was conducted from 2011 to 2012. There were 83 fish species indentified, there were 30 species unrecorded from 113 fish species reported by the previous authors. The total number of fish species revealed in the Boi basin river belongs to 77 genera, 30 families and 10 orders. Of the total families, the Perciformes is the most abundant one with 30%. The Cypriniformes comprises 39 genera, that takes 50.6% of the total of genera recorded, and 66 species, that takes 58.4% of the total species recoreded. Of the total fish species recoreded in the Boi basin river, there are 4 species listed in the Vietnam Red Data Book, 2007 with EN level, such as Clupanodon thrissa (Linnaeus, 1758) and Channa maculata (Lacepede, 1802); with VU level as Konosirus punctatus (Schlegel, 1846) and Bangana lemassoni (Pellegrin & Chevey, 1936). There are 75 species are listed in the IUCN Red List, 2012. Of those 4 species of VU level are Pseudohemiculter dispar (Peters, 1880), Cirrhinus cirrhosus (Bloch, 1795), Cyprinus carpio Linnaeus, 1758 and Cranoglanis sinensis Peters 1881; two species of NT level are Cirrhina molitorella (Cuv & Val, 1844) and Hypophthalmichthys molitrix (C. & V., 1844); level LC were 45 species and 24 species belong to the level DD.